2015
DOI: 10.1371/journal.pone.0140805
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cells Preconditioned with Hemin Are Less Permissive to Plasmodium Invasion In Vivo and In Vitro

Abstract: Malaria is a parasitic disease that causes severe hemolytic anemia in Plasmodium-infected hosts, which results in the release and accumulation of oxidized heme (hemin). Although hemin impairs the establishment of Plasmodium immunity in vitro and in vivo, mice preconditioned with hemin develop lower parasitemia when challenged with Plasmodium chabaudi adami blood stage parasites. In order to understand the mechanism accounting for this resistance as well as the impact of hemin on eryptosis and plasma levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…This contention is supported by Dalko et al, who observed a significant positive correlation between heme and parasite burden, as measured by HRP-2 levels [ 18 ]. Conversely, there is evidence that extracellular heme may limit the permissibility of red blood cells to merozoite invasion, thereby leading to lower parasitemia counts in both in vitro culture and in vivo mouse models [ 25 ]. This may also explain, at least partly, the association between severe malarial anemia and lower parasite burdens [ 21 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This contention is supported by Dalko et al, who observed a significant positive correlation between heme and parasite burden, as measured by HRP-2 levels [ 18 ]. Conversely, there is evidence that extracellular heme may limit the permissibility of red blood cells to merozoite invasion, thereby leading to lower parasitemia counts in both in vitro culture and in vivo mouse models [ 25 ]. This may also explain, at least partly, the association between severe malarial anemia and lower parasite burdens [ 21 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Confocal images were acquired with a Leica TCS SP8 fluorescence microscope and were further analyzed and extracted using LAS X (Leica) software. 62 Expression and Purification of Thioredoxin (Trx). E. coli BL21(DE3) cells were transformed with pJK615 (Addgene Plasmid #71699, produces E. coli Trx with a C-terminal His6 tag), individual colonies were inoculated in L.B.…”
Section: ■ Methodsmentioning
confidence: 99%
“…Differential interference contrast (DIC) images were taken to analyze the morphological changes in RBCs. Confocal images were acquired with a Leica TCS SP8 fluorescence microscope and were further analyzed and extracted using LAS X (Leica) software …”
Section: Methodsmentioning
confidence: 99%
“…The eryptosis in malignancy is stimulated, at least in part, by a plasma component. The percentage of eryptotic erythrocytes was significantly higher following exposure of healthy 10,11 Hepatic injury 12,13 Cardiac failure 14 Chronic kidney disease [15][16][17][18] Hemolytic uremic syndrome 1 Dehydration 19 Phosphate depletion 1 Calcitriol excess 20 Inflammation 21 Arteritis 22 Fever 23 Sepsis 24 Systemic lupus erythematosus 25 Mycoplasma infection 1 Malaria [26][27][28] Iron deficiency 29 Sickle cell anemia 30 Thalassemia 30 Glucose 6-phosphate dehydrogenase deficiency 31,32 Hereditary spherocytosis 2,23 Paroxysmal nocturnal haemoglobinuria 1 Wilsons disease 1 Parkinsons disease 33 Malignancy (see text).…”
Section: Enhanced Eryptosis In Malignancymentioning
confidence: 99%